‘Food desertification’: The loss of a major supermarket in New Haven, Connecticut - Russell, Scott E; Heidkamp, C Patrick (Applied Geography, 2011)
In March of 2010, the only full-service supermarket centrally located in New Haven, Connecticut closed, stranding many of the city's residents in a food desert. A food desert is an urban or rural area with significantly limited access to retail sources of healthy and affordable food, due to a combination of socioeconomic disadvantages and physical distance. This article considers the pivotal and causative role of the business model of supermarkets in the creation of new or exacerbation of current urban food deserts, as well as in the impact the loss of one market has on the resilience of the community's food system. Using the events of New Haven as a case study, the form and severity of the food desert in New Haven is analyzed by mapping 1/4 mile, 1/2 mile, and 1 mile road network service areas of the major supermarkets and grocery stores of the area. These are compared against Census block group data of the New Haven population's median household income, poverty level, and access to a personal vehicle. The results show certain parts of the city with low income, high poverty, and low vehicle access to exist in hardship outside the service areas of nearby stores. GIS methodology aids in illustrating the conclusion that the loss of just one supermarket has had significantly detrimental effects on the geographical food access of the city's residents. The ongoing lack of a full-service supermarket in the city not only raises concerns about the value of a new supermarket coming in, but also creates possibilities for seeking alternative food system solutions. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Connecticut; Food deserts; Food security; GIS; Geographic information systems (GIS); New Haven; Supermarkets; United States; Urban food systems; consumption behavior; dept.egm; food consumption; mapping method; retailing; spatial analysis

Astana, Kazakhstan: Megadream, Megacity, Megadestiny? - Yacher, Leon (Engineering Earth: The Impacts of Megaengineering Projects, 2011)
Astana, Kazakhstan’s new capital city is being built to fit the future vision of the country’s leaders. Unique architectural styles, combined with creative morphological patterns give the city a distinctive look. It is being constructed to impress. It also represents a break from the past. As such, Astana embodies the meaning of a ‘Forward city.’ Forward cities are created for a variety of reasons; political, geopolitical, religious, economic or a combination of these. By relocating a capital city elsewhere, a country seeks to construct a fresh urban site that reflects a change from the traditional center of governmental activities to a new location that reveals a new direction for the country and its people. This chapter provides a brief background of the political context and conditions existing in the region, followed by an overview of the city’s geographic base, and scrutinize the unique methods of finance used to construct Astana. Also, the planning and design of the city will be examined, paying special attention to the ways in which architecture has been utilized to construct a futuristic vision of a public project for domestic and international consumption.
Keywords: Capital City; Kyrgyz Republic; Presidential Decree; Soviet Republic; Special Economic Zone; dept.egm